4-Hydroxy-7-oxo-5-heptenoic Acid (HOHA) Lactone Induces Angiogenesis through Several Different Molecular Pathways - Guo, Junhong (Chem Res Toxicol, 2016)
Oxidative stress and angiogenesis have been implicated not only in normal phenomena such as tissue healing and remodeling but also in many pathological processes. However, the relationships between oxidative stress and angiogenesis still remain unclear, although oxidative stress has been convincingly demonstrated to influence the progression of angiogenesis under physiological and pathological conditions. The retina is particularly susceptible to oxidative stress owing to its intensive oxygenation and high abundance of polyunsaturated fatty acyls. In particular, it has high levels of docosahexaenoates whose oxidative fragmentation produces 4-hydroxy-7-oxo-5-heptenoic acid (HOHA)-lactone. Previously, we found that HOHA-lactone is a major precursor of 2-(ω-carboxyethyl)pyrrole (CEP) derivatives that are tightly linked to age-related macular degeneration (AMD). CEPs promote the pathological angiogenesis of late stage AMD. We now report additional mechanisms by which HOHA-lactone promotes angiogenesis. Using cultured ARPE-19 cells; we observed that HOHA-lactone induces secretion of vascular endothelial growth factor (VEGF), which correlated to increases in reactive oxygen species (ROS) and decreases in intracellular glutathione (GSH). Wound healing and tube formation assays provided, for the first time, in vitro evidence that HOHA-lactone induces the release from ARPE-19 cells of VEGF that promotes angiogenesis by human umbilical vein endothelial cells (HUVEC) in culture. Thus, HOHA-lactone can stimulate vascular growth through a VEGF-dependent pathway. In addition, results from MTT and wound healing assays as well as tube formation experiments showed that GSH-conjugated metabolites of HOHA-lactone stimulate HUVE cell proliferation and promote angiogenesis in vitro. Previous studies demonstrated that HOHA-lactone, through its CEP derivatives, promotes angiogenesis in a novel Toll-like receptor 2-dependent manner that is independent of the VEGF receptor or VEGF expression. The new studies show that HOHA-lactone also participates in other angiogenic signaling pathways that include promoting the secretion of VEGF from RPE cells.